Immune status characteristics in patients with hormonal disorders and undifferentiated connective tissue dysplasia - Chikisheva A.A (LCC «Medicine-Inform», 2019)
Immune status characteristics in patients with hormonal disorders and undifferentiated connective tissue dysplasia I.Yu. Ilina, Yu.E. Dobrokhotova, A.A. Chikisheva, V.O. Malikova Pirogov Russian National Research Medical University, Moscow, Russian Federation In recent decades, many papers on connective tissue dysplasia (CTD) were published. High occurrence, multiple organ lesion, and unfavorable (quite often) outcomes of this disorder account for its medical social importance. Structural and functional alterations resulted from CTD progression occur in various organs and tissues. They are accompanied by immune disorders, cellular, phagocytic, and humoral immune response deficiency. Aim: to assess the effect of enzyme therapy on immune alterations in reproductive age women with undifferentiated connective tissue dysplasia. Patients and Methods: 212 women of reproductive age with clinical manifestations of hyperandrogenism and infertility were enrolled in the study. Group I included 84 women with CTD signs (39.6%), group II included 128 women without CTD (60.4%). Both groups were subdivided into the subgroups depending on the hormonal abnormalities. IgA, IgG, IgM, IgЕ, circulating immune complexes, and C3 and C4 complement proteins were measured. Both groups received systemic treatment, Wobenzym (5 tablets 3 times a day for a month, then 3 tablets 3 times a day for 2 months). Results: the occurence of hyperandrogenism of various nature in women with and without CTD is almost similar. In women with CTD the occurence of genital prolapse is higher than in women with normal collagen metabolism. IgE levels in women with CTD are 1.5-times higher than in women without CTD. Moreover, these abnormalities were more severe in women with hormonal imbalance. Conclusion: women of reproductive age with CTD require metabolic therapy to normalize collagen synthesis in combination with systemic enzyme therapy since they are characterized by increased collagen breakdown. Some changes in immune parameters typical for connective tissue disorders may be revealed. Key words: immune status, connective tissue dysplasia, immunoglobulins, circulating immune complexes, systemic enzyme therapy. For citation: Ilina I.Yu., Dobrokhotova Yu.E., Chikisheva A.A., Malikova V.O. Immune status characteristics in patients with hormonal disorders and undifferentiated connective tissue dysplasia. Russian Journal of Woman and Child Health. 2019;2(1):23-27.